2021
DOI: 10.1002/hep.31739
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Significance of Hepatic CD69+CD103+CD8+ Resident‐Memory T Cells in Autoimmune Hepatitis

Abstract: BaCKgRoUND aND aIMS:The diverse inflammatory response found in the liver of patients with autoimmune hepatitis (AIH) is well established, but identification of potentially pathogenic subpopulations has proven enigmatic. appRoaCH aND ReSUltS: We report herein that CD69 + CD103 + CD8 + tissue-resident memory T cells (T RM ) are significantly increased in the liver of patients with AIH compared to chronic hepatitis B, NAFLD, and healthy control tissues. In addition, there was a significant statistical correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 47 publications
2
24
0
Order By: Relevance
“…In addition to the protective roles against diseases, evidence suggests that T RM cells also become activated after sensitization to self-antigens. Aberrantly activated T RM cells can induce autoimmune disorders, such as autoimmune hepatitis and psoriasis (4,14). In the respiratory system, T RM specifically activated by environmental allergens might underlie the development and worsening of allergic asthma and other airway diseases (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the protective roles against diseases, evidence suggests that T RM cells also become activated after sensitization to self-antigens. Aberrantly activated T RM cells can induce autoimmune disorders, such as autoimmune hepatitis and psoriasis (4,14). In the respiratory system, T RM specifically activated by environmental allergens might underlie the development and worsening of allergic asthma and other airway diseases (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Further studies are needed to elucidate the mechanisms underlying tissue-resident CD8 T cell–specific functions. Recent reports have also revealed that CD69+ CD103+ CD8 Trm-like cells accumulate locally in the liver in AIH 56 and in PSC. 57 Among Trm cells, the frequency of Trm-like phenotypes is higher in CD103+ CD69+ CD8 T cells around the bile duct than in CD69+ CD8 T cells in the liver tissue.…”
Section: Cd8 T Cells/nkt Cells/nk Cellsmentioning
confidence: 94%
“…According to the procedure described previously ( 27 ), formalin-fixed, paraffin-embedded liver tissues were used for immunohistochemistry (IHC) and immunofluorescence with the primary antibodies targeting at CD103, CD8, TGF-β, IL-15 (all anti-human, ab129202, ab17147, ab170874, ab55276, Abcam, Cambridge, United Kingdom), and FGL1 (anti-human, ab275091, Abcam; anti-mouse, 16000-1-AP, Proteintech, San Diego, CA, USA). Then information of antibodies could be found in the Supplementary table .…”
Section: Methodsmentioning
confidence: 99%
“…The flow cytometric was conducted as reported previously ( 27 ). For surface staining, the cells were cultured with antibodies specific for human cell surface markers CD3, CD4, CD8, CD103, CD69, LAG-3, PD-1, TIM-3, and CTLA-4 (564713, 564724,564116, 350225, 557745, 565775, 329920,…”
Section: Methodsmentioning
confidence: 99%